Building maintenance performance in operation & management at Setia Ecohill Mall, Semenyih / Muhammad Haziq Azhar and Alia Abdullah Saleh - Azhar, Muhammad Haziq; Abdullah Saleh, Alia (2023)
The aim of this research is to identify building maintenance performance in operation & management. The objective of the research is to identify the building maintenance in operation management and to determine the satisfaction from the maintenance team on the performance of the building. This study uses quantitative method which questionnaires will be distributed to the recognized respondents which is the maintenance worker at Setia Ecohill Mall, Selangor. This is such the most effective method in delivering research in collecting numerous data from the big population due to the limited time, cost, and transportation. The findings show that the majority of respondents are currently satisfied with building maintenance performance in operation and management. This thesis gives a comprehensive analysis of building maintenance performance indicators.